Literature Review: Efektivitas Konsumsi Tablet Tambah Darah dalam Menurunkan Risiko Anemia pada Ibu Hamil - Nurdiana Manurung; Lenny Sepriani Br Silalahi (Pusat riset dan Inovasi Nasional, 2025)
Iron-deficiency anemia during pregnancy remains a major public health concern in developing countries. This study aims to evaluate the effectiveness of iron and folic acid supplementation, known as iron tablets, in reducing the risk of anemia among pregnant women. A descriptive qualitative literature review method was employed by analyzing nine eligible studies published between 2013 and 2023. Articles were selected from databases including Google Scholar, PubMed, and ScienceDirect using specific keywords. The findings suggest that regular consumption of iron tablets, particularly starting in the second trimester and meeting the minimum recommended dose of 90 tablets, is effective in improving hemoglobin levels and lowering anemia prevalence. However, compliance remains a significant challenge, influenced by side effects, maternal knowledge, and social support. The review highlights the need for behavior-based interventions and family involvement to enhance adherence. The implication of this review supports the integration of targeted health education and follow-up strategies within antenatal care services to reduce anemia-related risks in pregnancy.